ANALISIS TINGKAT PEMAHAMAN MAHASISWA TERHADAP PERNYATAAN STANDAR AKUNTANSI KEUANGAN SYARIAH PSAK-SYARIAH - Purnama Putra (JRAK: Journal of Accounting Research and Computerized Accounting, 2015)
Sharia financial industries have grown rapidly in the last one decade. It causes the need of arrangingsharia accounting standard and human resources who understand the context of sharia based business becomesurgently required. Universities conducting high education services provide the students to meet the need ofsharia financial industries. Related to the provision of human resources with the understanding of shariaaccounting, Islamic Universities of 45 (Unisma) Bekasi gives two choices for the students to take either IslamicBanking or Accounting department focusing on sharia accounting. The research method employed in this study was descriptive quantitative. The primary data source wasthe written test containing 25 items consisted of 20 multiple choices and 5 essays. The sample was 23 students:8 were from sharia accounting department and 15 were from Islamic Banking in the academic year of 2012.The sample was taken by using purposive sampling technique since the sample was only those having takensharia PSAK. The method used for data analysis was by scoring the test result and converting it to the scorebased on the standard scoring of UNISMA. Based on the average score of the test done by the students of ShariaAccounting which was 72.93, the students "understand" sharia PSAK while the students of 2012 academic yearmajoring in Islamic Banking have the average score was 77 which also means that the students "understand"sharia PSAK. The hypothesis was tested by using Mann Whitney Test with the Sig value (p value) of 0.084 >0.05meaning that there is no difference between the understanding of the students who were focusing in ShariahAccounting and majoring in shareea banking belonging to the academic year of 2012 on sharia PSAK. It meansthat H alternative is rejected while H0 is accepted.